2023
DOI: 10.1029/2023ef003626
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Stratospheric Aerosol Injection on Extreme Fire Weather Risk

Abstract: Stratospheric aerosol injection (SAI) would potentially be effective in limiting global warming and preserving large‐scale temperature patterns; however, there are still gaps in understanding the impact of SAI on wildfire risk. In this study, extreme fire weather is assessed in an Earth system model experiment that deploys SAI beginning in 2035, targeting a global temperature increase of 1.5°C above pre‐industrial levels under a moderate warming scenario. After SAI deployment, increases in extreme fire weather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Aluminum nanoparticles are also well known for their pyrophoric capacity and the high energy they emit during combustion [102], thus amplifying the risk and severity of wildfires. In addition, geoengineering simulations showed that SAI induces drought [103], leading to an increase in the frequency of extreme fires in some regions [104].…”
Section: Wildfiresmentioning
confidence: 99%
“…Aluminum nanoparticles are also well known for their pyrophoric capacity and the high energy they emit during combustion [102], thus amplifying the risk and severity of wildfires. In addition, geoengineering simulations showed that SAI induces drought [103], leading to an increase in the frequency of extreme fires in some regions [104].…”
Section: Wildfiresmentioning
confidence: 99%
“…However, this analysis is limited as it looks at annual precipitation rather than looking at droughts, with the latter a much stronger driver of Amazon tipping. Touma et al , (2023) uses an SAI scheme to keep temperature close to 1.5 O C above pre-industrial, and sees increases in drying and fires in the West Amazon when compared to SSP2-4.5, whilst a reduction in fires in Northeast Brazil, which includes part of the East Amazon. However, drought severity is found to increase slightly for both regions under SRM when compared to SSP2-4.5.…”
Section: 32: the Impacts Of Srmmentioning
confidence: 99%